2022
DOI: 10.1002/smll.202202134
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Reversible Reaction by Uniform Distribution of Heterogeneous Intermediates on Defect‐Rich SnSSe/C Layered Heterostructure for Ultralong‐Cycling Sodium Storage

Abstract: 2D layered Sn‐based materials have attracted enormous attention due to their remarkable performance in sodium‐ion batteries. Nevertheless, this promising candidate involves a complex Na+‐storage process with multistep conversion‐alloying reactions, which induces the uneven dispersion of heterogeneous intermediate accompanied by severe agglomeration of metallic Sn0, inescapably resulting in poor reaction reversibility with sluggish rate capability and inferior cyclic lifespan. Herein, a delicately layered heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…[24,26,27] Such an expanded interplanar spacing can effectively reduce the energy barrier during K-ion intercalation and diffusion in FeNiS solid solution, in terms of enhanced reaction kinetics. [28,29] Ulteriorly, the bright rings in the select area electron diffraction (SAED) pattern (inserted in Figure 1d) are consistent well with the (100) and (001) characteristic planes of the NiS phase, respectively. Moreover, Fe, Ni, and S elements are evenly distributed and nearly overlap each other in the individual skeleton particle in the EDS mapping image (Figure 1g and Figure S6, Supporting Information) and the ratio of Fe to Ni elements in the FNS/C composites is calculated to be close to 0.4:0.6 based on the result in Table S1, Supporting Information.…”
Section: Resultssupporting
confidence: 64%
“…[24,26,27] Such an expanded interplanar spacing can effectively reduce the energy barrier during K-ion intercalation and diffusion in FeNiS solid solution, in terms of enhanced reaction kinetics. [28,29] Ulteriorly, the bright rings in the select area electron diffraction (SAED) pattern (inserted in Figure 1d) are consistent well with the (100) and (001) characteristic planes of the NiS phase, respectively. Moreover, Fe, Ni, and S elements are evenly distributed and nearly overlap each other in the individual skeleton particle in the EDS mapping image (Figure 1g and Figure S6, Supporting Information) and the ratio of Fe to Ni elements in the FNS/C composites is calculated to be close to 0.4:0.6 based on the result in Table S1, Supporting Information.…”
Section: Resultssupporting
confidence: 64%
“…Consequently, as the S 2− content increases, the lattice constants along the c-axis decrease. [20][21][22] Importantly, the absence of impurity diffraction peaks highlights the high purity achieved through microwave synthesis. The composition of SnSe 2 /N-C, SnS 1.5 Se 0.5 /NS-C, and SnS 2 /N-C was further confirmed by Raman spectroscopy in Figure 1b,c.…”
Section: Resultsmentioning
confidence: 99%
“…Their layered structure, along with multiple ways of sodium storage, including alloying, conversion, and intercalation, make them highly favorable. [7][8][9] Although some studies have explored the failure mechanism of Sn-Mx anodes and the layered structure can enhance sodium ion diffusion, there still exist capacity decay and irreversible capacity in practical applications, as well as a failure to achieve the expected cycle life. [7,10] Extensive studies have revealed that intermediates (Sn 0 and Na x M) nucleate and grow during the conversion reaction of SnM x and Na + in SIBs, leading to agglomeration that hinders the reverse reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of highly electrically conductive phases and the creation of lattice boundary/interfaces to accelerate the Na + /e − diffusion have proven to be effective ways to address these problems. 8,9 In SnS 2 , Sn displays its highest valence state and S its lowest—and crystal boundary/interfaces may be formed here by redox reactions, with transition metals serving as suitable reductants. To convert SnS 2 to highly conductive, fast Na + diffuse anodes, in the current work, a DFT calculation was performed to guide the materials synthesis, and Fe was applied as an example reductant due to its being a relatively inexpensive metal.…”
mentioning
confidence: 99%